2017
DOI: 10.1002/jemt.22840
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide 3Dmicrostructures as an antimicrobial filler content for composite resins

Abstract: The aim of this study was to evaluate the antibacterial activity of a composite resin modified by 3D zinc oxide (ZnO) microstructures and to verify possible alterations on its mechanical properties. ZnO was synthesized by hydrothermal approach and characterized by X-ray diffraction (XRD), surface area by Brunauer, Emmett and Teller (BET), Fourier transform infrared spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM). The minimum inhibitory concentrations of ZnO against Streptococcus mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…The antibacterial filler introduction had no statistically significant effect on DTS, although the mean value for the control group was the lowest. Those findings are in opposition to the results obtained by Łukomska-Szymańska et al [ 101 ], Diaz et al [ 102 ], and Sokołowski et al [ 103 ], where nonfunctionalized calcium fluoride microparticles, zinc oxide three-dimensional microstructures, nanosilver, and nanogold decreased the DTS values of modified composites.…”
Section: Discussioncontrasting
confidence: 83%
“…The antibacterial filler introduction had no statistically significant effect on DTS, although the mean value for the control group was the lowest. Those findings are in opposition to the results obtained by Łukomska-Szymańska et al [ 101 ], Diaz et al [ 102 ], and Sokołowski et al [ 103 ], where nonfunctionalized calcium fluoride microparticles, zinc oxide three-dimensional microstructures, nanosilver, and nanogold decreased the DTS values of modified composites.…”
Section: Discussioncontrasting
confidence: 83%
“…Numerous studies have been conducted to improve antibacterial properties for dental restoration materials, such as fluorides [15,30,31], zinc ions [32,33,34,35], silver nanoparticles and silver ions [18,20,25,26,36], and quaternary ammonium groups [25,26,37] are introduced into the fillers through different reaction mechanisms to enhance antimicrobial functions of composite resins. In this study, as the silver content in the resin matrix increased, the antibacterial effect of the resin became more and more significant.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that resin composites incorporating ZnO presented antibacterial activity against S. mutans and S. sobrinus 9 , 31 . However, these works have used commercially available resin composites to test this possibility.…”
Section: Introductionmentioning
confidence: 99%